Integration with cultures and micro-clonal breeding of strawberries in the conditions of “in vitro” - Allayorov Abdurokhman; Zuparov Mirakbar; Yuldoshov Shavkat; Buronov Fakhriddin (E3S Web of Conferences, 2023)
Strawberries (Fragaria x ananassa Duch.) are exposed to the world and is 70% of the world's breeding fruits in the world. The cultivation of strawberries is growing every year, now the yield of this crop has exceeded 4 million tons per year. The article was tested by various concentration of sodium hyphosts for steriles in the article. Nutrients containing nitrogen, phosphorus, potassium, calcium, sulfur, magnesium, iron and trace elements: boron, zinc, copper, cobalt, manganese, iodine, molybdenum, as well as vitamins, carbohydrates, carbohydrates, and phytohormones are used for growing plants. Casein hydrolyzate and some amino acids are added to some food media. In addition, EDTA (ethylenediamine-tetraacetic acid) or its sodium salt is added to the nutritional medium to meet the iron needs of the cells. In the sterulation of strawberries plant, the affected plants were 16.3%, and the survival rate was 83.7%, when carried out in the solution of the surface in sterulation of the surface. In micro-clonal breeding, the development of plants in the options of BAP +2 and NAA + 1 in the options added to 89.7% were 89.7%.